(untitled) (Research, Society and Development, 2021)
The objective was to investigate the profile and methodological approach of articles published by the scientific nursing community related to teenage pregnancy in order to identify strategies for the prevention of early pregnancy. To this end, an integrative literature review was carried out through consultation at the Virtual Health Library (VHL), through the descriptors "teenage pregnancy" and "nursing care", selecting papers published in the last five years. It was found that 70% of the studies were descriptive in nature, being 60% of qualitative approach. Regarding the demographic profile, the predominant variables were age in 100% of the articles, schooling and marital status in 70% and family income in 50%. The prevention strategies proposed to reduce cases of early pregnancy highlighted sexual counseling and health education for adolescents and professionals, as well as the strengthening of bonds between young people and the team. It was concluded that there was a wide coverage of aspects addressed about teenage pregnancy and that the researches sought not only to analyze the view of nurses, but also pregnant women, and aimed to elucidate resolutive care actions.